Binge eating and binge drinking behaviors: the role of family functioning. Issue 4 (21st April 2021) - Laghi, Fiorenzo; Bianchi, Dora; Pompili, Sara; Lonigro, Antonia; Baiocco, Roberto
ABSTRACT: Binge eating and binge drinking are two of the most common health-risk behaviors among young people showing to frequently co-occur in nonclinical samples of adolescent boys and girls. The present study examined the role of different dimensions of family functioning in binge behaviors among adolescents. One thousand and twenty young to late adolescents (507 girls and 517 boys) with ages ranging from 16 to 22 years participated in the study and completed a survey of self-report measures. Our findings showed that adolescents who binge eat and drink and adolescents who only binge eat perceived a lower quality of family functioning with lower levels of cohesion, flexibility, communication, satisfaction and higher degree of disengagement compared to adolescents who do not binge and adolescents who only binge drink. Only adolescents who engage in both binge behaviors reported higher levels of chaotic style compared to other binge groups. Furthermore, living in families poorly flexible, highly disengaged and with communication problems among members resulted as risk factors for binge eating behavior. Results suggest the importance for prevention programs to be based on an integrated approach focused on improving family environment such as the ability in changing family structure to deal effectively with developmental problems and defining clear home rules adolescents may stand on.